Available bandwidth estimation metrics as tools to evaluate network trunk links (2020)
Nowadays the platform par excellence for the development of all telecommunication activities is the Internet; and its infrastructure is facing new challenges every day due to the growth in demand for more content, such as streaming video, storage, and cloud processing. Also, to maintain optimal levels of service quality, network applications demand more telecommunication resources. Similarly, the network infrastructures that support these applications have evolved, and demand greater and more efficient management of the trunk links, which play a primary role in sustaining services. Therefore, this paper presents the performance evaluation of trunk, wired and wireless links in a heterogeneous computer network infrastructure, using available bandwidth estimation tools such as IGI, Pathload, and Traceband. Thus, for the experimental evaluation of the trunk links, two real network scenarios were implemented, where crosstraffic was generated in a synthetic way using the Mgen tool. Consequently, this study allowed verifying in other aspects; that the metrics of the estimation tools can be used to evaluate and know the performance of wired and wireless trunk links, which can be reliable up to 96% for network administrative tasks.